Post-pandemic obesity: prevalence and waist circumference cut-off point in a peruvian region - Soto-Cáceres, Víctor Alberto (2025)
Objectives: To describe the prevalence of obesity according to BMI in the adult population between 25 and 59 years of age, post-COVID-19 pandemic, and to specify the waist circumference cut-off point for obesity diagnosis. Material and methods: Descriptive cross-sectional study, sample 384 people, probabilistic sampling in six districts of the Lambayeque Region. With the approval of the USMP ethics committee and informed consent was applied to the participants. Results: The frequency of obesity was 28.4% (27.1% males and 29.5% females), 50.2% overweight with a statistical difference according to sex. Obesity is higher in Ilimo district 50.01%. The ROC curve was used to identify waist circumference cut-off points: 97.50 cm in males, 89.6% sensitivity and 80.0% specificity and 92.50 cm in females, 88.5% sensitivity and 70.5% specificity. Conclusions: One in four adults is obese and the cut-off point for the waist circumference of men is 97.5 cm and that of women is 92.5 cm.